Childbirth Experience Associated With Maternal and Paternal Stress During the First Year, but Not Child Attachment - Holopainen, Annaleena; Verhage, Marije L.; Oosterman, Mirjam (Frontiers in Psychiatry, 2020)
Women, as well as their partners, can experience childbirth in many different ways. A negative childbirth experience may have adverse effects on the entire family, resulting, for instance, in parental stress symptoms and a weakened parent-child relationship. Parental stress, without sufficient resources to compensate for it, may also in and of itself negatively influence the parent-child relationship. This study contributes to the current knowledge of the psychological effects of childbirth experience by using longitudinal data collected with both self-reports and observational measures, as well as multiple informants (i.e., mothers and partners). The aim of this study was to investigate whether 1) women’s retrospective birth experiences were related to maternal and paternal parenting stress, 2) birth experience was indirectly associated with child attachment via maternal stress, and 3) birth experience was directly related to child attachment. Data were collected from a mixed sample of community and at-risk primipara women (N = 1,364), as well as from their partners and children. Retrospective childbirth experience was measured 3 months postpartum with a latent factor consisting of five items asking about the feelings that women have about their childbirth. Parental stress was measured at 3 months postpartum for partners and 3 and 12 months postpartum for mothers using the adult domain of the parental stress index (PSI). Finally, parent-child attachment is observed in a subsample of 223 women and children at 12 months postpartum with the Strange Situation Procedure (SSP). Results show that women’s birth experience was significantly related to both mothers’ and their partners’ parenting stress. However, birth experience was not related to child attachment, neither directly nor indirectly via maternal stress. These findings emphasize the long-lasting impact that childbirth may have on both parents. Future research is still needed to further investigate which protective factors may weaken the association between birth experience and parental stress.